THE ESTIMATION OF MICROALGAE CULTIVATION PRODUCTIVITY FOR BIOFUEL PRODUCTION IN NIGERIAN CONDITIONS - Boichenko, Sergii; Shamanskyi, Sergii; Christiana, Adeniyi (Science-based technologies, 2019)
Microalgae constitute the main source of materials that can be used as raw materials for many high value bioproducts, the most prominent ones of which are vitamins, lipids, chlorophyll and carotenoids.The key to economic production of biomass and bioproducts from microalgae is to optimize their growth conditions. Microalgae require optimal lighting conditions for efficient photosynthesis. This article focuses on the conditions for growing microalgae mostly chlorella sp. Microalgae require optimal lighting conditions for efficient photosynthesis. Photoperiod, light intensity and wavelength of light are some of the important factors affecting the rate of photosynthesis. Light conditions directly affect the growth, pigment content and protein amount in microalgae. The aim of this paper is to model the productivity of biomass and the accumulation of lipids in algae, as well as to calculate the productivity when cultivated under weather conditions in different regions of Nigeria.The intensity of solar radiation per day is usually one of the variables collected by meteorological stations in Nigeria. Satellite derived solar irradiance over 25 locations in the 5 climatic zones of Nigeria (tropical rainforest, Guinea savannah , Sahel savannah , Sudan savannah , and Mangrove swamp forest ) was analyzed. This article analysis the prospect of production of biofuel of the third generation using microalgal biomass in the weather conditions typical regions of Nigeria. Taking into account the average monthly density of solar radiation in the main regions of Nigeria kWh/m2 .day to estimate the possibiity of achieving crop yields of microalgal biomass per square meter of cultivated areas in the weather conditions of Nigeria. In addition, advantages and current limitations of biodiesel production, quantitative and qualitative feasibility of microalgal biodiesel, and its economic feasibility are discussed.